(3CUhd GdeMGSHI GdeGdjI (B((3L(B1)s - (3MSGe GdOjf eUWai(B, (3GdNOGTs; (3hdjO RcQjG UjGe(B;(3YHO GdfGUQ GHQGgje fhQ(B, s ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2009)
(3eONd Gdi Yde GdeMGSHI GdeGdjI(B- (3JMdjd GdYedjGJ GdeGdjI(B- (3GdOaGJQ GdeMGSHjI(B- (3GdYedjGJ GdJehjdjI hGdQCSeGdjI(B- (3YedjGJ GdHVGYI(B- (3GdNUe(B- (3GdChQGb GdJLGQjI(B- (3ejRGf GdeQGLYI(B- (3GdMSGHGJ GdNJGejI hcTa GdejRGfjI GdYehejIs
(3HHdjhZQGajG(B: (3U(B.395 (3; W(B.1 1998s
Keywords: (3GdChQGb GdJLGQjIs; (3GdQCSeGdjIs; (3GdeMGSHI GdeGdjIs; (3eQGLYI GdMSGHGJs